(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Dhaka Zoo with 2000 animal heads of 184 species from significant genetic diversity and five million visitors influx round the year is placing it a public health important spot. This study was conducted to investigate aspergillosis in animals at Dhaka Zoo to ascertain animal health, welfare and public health safety standard. One hundred and two necropsied tissue samples preserved in 10% neutral buffered formalin at necropsy from 36 animals of 25 different species were collected from Dhaka Zoo. Twenty five out of 36 study animals were suffering from granulomatous diseases. Among them 13 animals were suffering from Aspergillosis. Clinical history, nodular lesions from necropsy findings, granulomatous reactions along with fungal spores and characteristic radiating club on histopathology; dichotomously branching septate hyphae and mycelial conidiophore on special staining were revealed Aspergillosis in 13 animals of nine species that includes four rhesus macaques (Macaca mulatta), two samber deer (Cervus unicolor) and one of each species were nilgai (Boselaphus tragocamelus), horse (Equus caballus), stripped hyena (Hyena hyena), gayal (Bos frontalis), beisa oryx (Oryx beisa beisa), water buck (Kobus L. leche) and greater kudu (Tragelaphus strepsiceros). Present study provides evidence of existing Aspergillosis and similar long standing zoonotic diseases in majority of rest of the animals with health risk that shades health safety standard at Dhaka Zoo. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19924 J. Bangladesh Agril. Univ. 11(2): 265-270, 2013